Does Women’s Role Have an Influence on Economy Growth in Indonesia? - Detris Sulisto; Nurhayati Nurhayati; Syafri Syafri; Samuel Fery Purba; Kezia Br Aritonang (Economics Development Analysis Journal, 2023)
Economic growth is one of the goals that every country strives for because it is a measurement of a country's success. Gender equality and gender empowerment are important goals for Indonesia's development and economic growth. The purpose of this study is to examine the effect of women’s role on the indicators of the gender development index, gender empowerment index, women's life expectancy, mean years of schooling for women, and women's income contribution to gross regional domestic product (GRDP), which is a proxy for Indonesian economic growth. This quantitative study uses a panel data regression model, secondary data from Statistics Indonesia, time series data from 2014 to 2021 and cross-section data for 34 provinces in Indonesia. The study's findings yielded 272 observations. Empirical results show that all indicators used to measure women's role, namely gender development index, gender empowerment index, women's life expectancy, mean years of schooling for women, and women's income contribution, have a positive and significant effect on Indonesia’s economic growth. The findings of the study show the Indonesian government's dedication to increasing women's role in various economic sectors in Indonesia. The influence of women's roles indicates additional household income and economic growth.